Back Cover: Crystal Structures and Phase‐Transition Dynamics of Cobaltocenium Salts with Bis(perfluoroalkylsulfonyl)amide Anions: Remarkable Odd–Even Effect of the Fluorocarbon Chains in the Anion (Chem. Eur. J. 20/2013). Issue 20 (2nd May 2013) - Mochida, Tomoyuki; Funasako, Yusuke; Inagaki, Takashi; Li, Meng‐Jiao; Asahara, Kotaro; Kuwahara, Daisuke
<x xml:space="preserve">Abstract</x> A remarkable odd–even effect in their crystal structures and melting entropies is observed for cobaltocenium salts with bis(perfluoroalkylsulfonyl)amide (CnF2n+1SO2)2N anions (n=0–4). In the salts with even n, the cations and anions are stacked alternately to form mixed columns, whereas the cations and anions form segregated columns in the salts with odd n. For more details on the structures and properties of these compounds see the Full Paper by T. Mochida et al. on page 6257 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>